2022
DOI: 10.1097/md.0000000000031206
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analytical evidence of functional and structural abnormalities associated with pain processing in migraine patients: An activation likelihood estimation

Abstract: Background: Migraine is a primary headache disorder that causes debilitating throbbing pain. Several functional MRI (fMRI) and voxel-based morphometry (VBM) studies have been used to investigate the structural and functional alteration in migraine. Here, we aim to study the converged brain regions of functional and structural abnormalities in gray matter volume (GMV) associated with pain processing and management in migraineurs and healthy controls (HC).Methods: A systematic search through PubMed and Sleuth wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In our cases, only two of six patients experienced the fremanezumab's efficacy. The older age of the patients may suffer from the longer duration of migraine, together with CM and MOH, leading to changes in the brain's structure [ 18 , 19 ] and making it more difficult for the CGRP-mABs to be effective. In such cases, erenumab, which has been suggested to have the potential to improve the functional structure of the brain [ 20 ], maybe a better choice.…”
Section: Discussionmentioning
confidence: 99%
“…In our cases, only two of six patients experienced the fremanezumab's efficacy. The older age of the patients may suffer from the longer duration of migraine, together with CM and MOH, leading to changes in the brain's structure [ 18 , 19 ] and making it more difficult for the CGRP-mABs to be effective. In such cases, erenumab, which has been suggested to have the potential to improve the functional structure of the brain [ 20 ], maybe a better choice.…”
Section: Discussionmentioning
confidence: 99%
“…Interictally, migraine without aura patients showed significantly lower gray matter density in the right inferior parietal lobule, right temporal inferior gyrus, right superior temporal gyrus, and left temporal pole compared to healthy volunteers. Ictally, gray matter density increased in the left temporal pole, bilateral insula, and right lenticular nuclei, with no areas showing decreased gray matter density Al Qawasmeh et al [46] Meta-analysis Migraine without aura patients showed a grey matter volume reduction in the insula and anterior cingulate, whereas migraine with aura patients showed a grey matter volume reduction in the cerebellum, cingulate gyrus, and insula.…”
Section: Coppola Et Al [45] Cohortmentioning
confidence: 99%
“…Research has indicated that migraine alters the activity of brain structures involved in memory processing and consolidation, including the insula [ 43 , 45 ]. Al Qawasmeh et al found that patients with migraine without aura exhibited a reduction in grey matter volume in the insula and anterior cingulate, while those with migraine with aura showed grey matter volume reduction in the cerebellum, cingulate gyrus, and insula [ 46 ]. Insular changes in chronic pain, particularly in patients with trigeminal neuralgia, involve modifications in gray matter volume.…”
Section: Reviewmentioning
confidence: 99%